Transanal Endorectal Pullthrough for Hirschsprungs Disease Without Frozen-Section Biopsy Facility (BIRDEM Medical Journal, 2014)
Objective: The purpose of this study was to evaluate results of treatment of patients with Hirschsprungs disease (HPD) by transanal endorectal pull-through (TEPT) in a setting where frozen-section biopsy facility was not available.Methods: From November 2001 to September 2007, fortytwo patients with HPD had undergone TEPT in Rajshahi Medical College Hospital (RMCH) and at various clinics in Rajshahi. The age of the patients ranged from 7 days to 12 years. In all cases, the extent of aganglionosis was limited to recto-sigmoid region and was assessed by the three classical features of contrast enema namely spastic aganglionic zone, transition zone (TZ) and proximal dilated zone (PDZ). During operative pull-through, transition zone (TZ) and proximal dilated zone (PDZ) were identified by naked eye and correlated with x-ray findings. Eleven patients had colostomy fashioned prior to the TEPT procedure. Followup was done for 14 to 58 months (mean 36 months).Result: Thirty-nine patients had satisfactory outcome without any complication. The mean operative time was 100 minutes. The average length of resected gut was 22 cm. Post-operative recovery was smooth and oral feeding was resumed after a mean period of 48 hours. Of the eleven children with colostomy, 6 were older than 10 years with huge megacolon, and the remaining five had their colostomy done at the referring hospital. In 4 patients out of 42, naked eye assessment of the TZ and PDZ and their correlation with the x-ray features were not possible. In such situation, a few cm more of the proximal ganglionic gut from PDZ was resected. Three children out of 42 developed complications; postoperative enterocolitis in two and intra-abdominal bleeding from sigmoid mesocolon in one. There was no incidence of cuff abscess, anastomotic leak, retained segment, encopresis or constipation.Conclusion: The minimal invasive procedure TEPT involves less time with trifle morbidity and offers rapid recovery with shorter hospital stay. The functional outcome is also excellent with small complication rate. The naked eye correlation of the morbid features of rectum and colon in HPD with classical x-ray features is reasonably consistent and TEPT can safely be performed where frozen-section facility is not available.Birdem Med J 2014; 4(2): 84-87